A report on the creative writing workshop for form 5 students of Maktab Rendah Sains MARA Perlis: Preliminary investigation - Mohamad, Mutiara (Universiti Utara Malaysia, 1992)
A creative workshop spanning a period of three months was conducted in Maktab Rendah Sains MARA Beseri, Perlis. 25 students randomly selected among those sitting for the July 1993 English 1119 paper were trained in the areas of rhetoric, sense awareness, grammar and mechanics and creativity as components for enriching their essay writing skills. The aim of this ethnographic study was to ascertain the effectiveness and richness of the subjects writing after having gone through the systematic training in those aforementioned skills. A preliminary analysis of the products or written work, consisting of a series of short writing, revealed a certain amount of richness in them. The student writer although worked from strict models of written work - established corpus - imitating the logical flow and creative instances of the models evidently demonstrated personal creativity in their work. Further work needs to be done with a more deliberate systematic experimental design which compares control and experimental groups, in order to delineate the areas of treatment which directly contribute to specific areas of improvement in writing skills.